The Implementation of Flipped Classroom using Screencast-O-Matic to Improve Students’ Verbal Linguistic Intelligence - Hasanudin, Cahyo; Fitrianingsih, Ayu; ., . (International Journal of Engineering and Technology, 2018)
This research aims to 1) implement flipped classroom model using screencast-o-matic, 2) investigate the improvement of verbal linguistic intelligence through the implementation of flipped classroom model using screencast-o-matic for the students of IKIP PGRI Bojonegoro in academic year 2017-2018. This research is classroom action research (CAR) conducted at IKIP PGRI Bojonegoro, the subjects of the research are the first year students in second semester of academic year 2017-2018. The indicators of the research are measured using N-Gain test with the normalized Gain index interpretation category. Data sources in this research are 1) learning activities 2) informants, 3) documentary data. Data collection technique used documentation methods,observations, and verbal linguistic test of Thomas Armstrong by using Likert scale. The results of this research show that 1) the implementation of flipped classroom uses six stages, 2) the improvement of students’ verbal linguistic intelligence can be seen from the actions in every cycle. In the preliminary research, the researcher had measured the students’ learning styles, from 30 students who were the subject of research. There were 6 students who had visual learning style, 7 students had auditory learning style, and 17 students had kinesthetic learning style. In cycle I, FLIP model is implemented and students’ verbal linguistic intelligence is 61,43. In cycle II, students’ verbal linguistic intelligence is 81, 03. The conclusion of this research are 1) the the implementation of flipped classroom model using Screencast-O-Matic uses FLIP model, 2) the improvement of students’ verbal linguistic intelligence in IKIP PGRI Bojonegoro can be classified into average category.